Human lung adenocarcinoma cell cultures derived from malignant pleural effusions as model system to predict patients chemosensitivity. Issue 1 (December 2016) - Roscilli, Giuseppe; Vitis, Claudia; Ferrara, Fabiana; Noto, Alessia; Cherubini, Emanuela; Ricci, Alberto; Mariotta, Salvatore; Giarnieri, Enrico; Giovagnoli, Maria; Torrisi, Maria; Bergantino, Francesca; Costantini, Susan; et al.
Abstract Background Lung cancer is the leading cause of cancer related deaths and Malignant Pleural Effusion (MPE) is a frequent complication. Current therapies suffer from lack of efficacy in a great percentage of cases, especially when cancer is diagnosed at a late stage. Moreover patients' responses vary and the outcome is unpredictable. Therefore, the identification of patients who will benefit most of chemotherapy treatment is important for accurate prognostication and better outcome. In this study, using malignant pleural effusions (MPE) from non-small cell lung cancer (NSCLC) patients, we established a collection of patient-derived Adenocarcinoma cultures which were characterized for their sensitivity to chemotherapeutic drugs used in the clinical practice. Methods Tumor cells present in MPEs of patients with NSCLC were isolated by density gradient centrifugation, placed in culture and genotyped by next generation sequencing. In a subset of cases patient derived xenografts (PDX) were obtained upon tumor cell inoculation in rag2/IL2 knock-out mice. Isolated primary cultures were characterized and tested for drug sensitivity by in vitro proliferation assays. Additivity, antagonism or synergy for combinatorial treatments were determined by analysis with the Calcusyn software. Results We have optimized isolation procedures and culture conditions to expand in vitro primary cultures from Malignant Pleural Effusions (MPEs) of patients affected by lung adenocarcinomas, the most frequent form of non small cell lung cancer. Using this approach we have been able to establish 16 primary cultures from MPEs. Cells were banked at low passages and were characterized for their mutational pattern by next generation sequencing for most common driver mutations in lung cancer. Moreover, amplified cultures were shown to engraft with high efficiency when injected in immunocompromised mice. Cancer cell sensitivity to drugs used in standard chemotherapy regimens was assessed either individually or in combination. Differential chemosensitivity and different mutation profiles were observed which suggests that this isolation method could provide a platform for predicting the efficacy of chemotherapy in the clinical setting. Most importantly for six patients it was possible to establish a correlation between drug response in vitro and response to therapy in the clinic. Conclusions Results obtained using primary cultured cells from MPEs underscore the heterogeneity of NSCLC in advanced stage as indicated by drug response and mutation profile. Comparison of data obtained from in vitro assays with patients' responses to therapy leads to the conclusion that this strategy may provide a potentially useful approach for evaluating individual chemosensitivity profile and tailor the therapy accordingly. Furthermore, combining MPE-derived primary cultures with their genomic testing allows to identify patients eligible to trials with novel targeted agents.